Exploration Six Ways of Being Religion According to Dale Cannon Based on An Islamic Perspective - Arzaqi, Argha Zidan (International Journal of Islamicate Social Studies, 2024)
This research aims to provide knowledge development regarding the exploration of religious procedures according to Dale Cannon using an Islamic perspective. The data collecting technique is library research using a qualitative approach. Dale Cannon identified in his book "Six Ways of Being Religious." This research focuses on exploring six ways of religion from an Islamic perspective, including: 1) sacred rites including prayer, fasting, zakat, hajj; 2) do good/right action, namely a good relationship with God and fellow humans; 3) devotion, namely faith and piety; 4) reasoned inquiry to gain knowledge and wisdom; 5) mystical quest include intuitive experiences, ascetic discipline and 6) Samanic mediation in the form of dhikr and remembering Allah. Each of these ways of religion reflects a different approach to spirituality and religious life and an understanding of them can help in detailing and understanding variations in religious practice across communities and individuals.